Pengaruh Penggunaan Birthing Ball Terhadap Kemajuan Persalinan pada Ibu Bersalin Kala I di Klinik Pratama ST Fransiskus Asisi Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Tahun 2024 - Rimbun Purba1; Nopalina Suyanti Damanik; Ester Simanullang; Riska Susanti Pasaribu (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The birth ball is a physical therapy ball that helps mothers in the first stage in the progress of labor and can be used in various positions. One of the movements is sitting on the ball and rocking back and forth which makes you feel comfortable and helps progress labor by using gravity while increasing the release of endorphins because the elasticity and curvature of the ball stimulates the receptors in the pelvis which are responsible for secreting endorphins (Kurniawati, 2017). This research aims to determine the effect of using a birth ball on the progress of labor among women in the first stage of labor at the ST Fransiskus Assisi Pratama Clinic, Sei Tuan District, Deli Serdang Regency in 2024. This type of research is research using a quasi-experimental research method (quasi-experiment) with a pretest-design. posttest. The population and sample are all pregnant women from TM III Kenangan Health Center, Medan Denai District, Medan City in 2024 in May-June, as many as 32 people using the Purposive Sampling technique using the Chi Square statistical test. It was concluded that based on the results of the Chi Square test analysis, a significance value of 0.018 was obtained. Based on this value, because the p value <0.05, it could be concluded that the birth ball had an effect on the progress of labor in mothers in the first stage of labor at the ST Fransiskus Asisi Pratama Clinic, Sei Tuan District, Deli Serdang Regency, Year 2024